Does Health Insurance Make People Happier? Evidence from Massachusetts' Healthcare Reform - Seonghoon Kim; Kanghyock Koh (Institute of Labor Economics (IZA), 2018)
We study the effects of Massachusetts' healthcare reform on individuals' subjective well-being. Using data from the Behavioral Risk Factor Surveillance System, we find that the reform significantly improved Massachusetts residents' overall life-satisfaction. This result is robust to various sensitivity checks and a falsification test. We also find that the reform improved mental health. An additional analysis on the Tennessee healthcare reform supports our findings' external validity. Using the reform as an instrument for health insurance coverage, we estimate its large impact on overall life-satisfaction. Our results provide novel evidence on the psychological consequences of Massachusetts' healthcare reform.
Keywords: I13; I18; I31; 330; health insurance; life satisfaction; happiness; subjective well-being; Massachusetts healthcare reform